Development of Reaction Rate Animation Application (Alare) to Train Students' Critical Thinking Skills on Reaction Rate Material - Sudiyono, Achmad Farichi; Sukarmin, Sukarmin (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The purpose of this research is to produce an Alare application that is feasible to use to train students' critical thinking skills in the sub-material of factors that affect the reaction rate. The feasibility of the Alare application is reviewed from three aspects, namely validity, practicality, and effectiveness. This research used the Research and Development (R&D) method with the Sukmadinata development model. The limited trial was conducted in class XI IPAS of Senior High School 20 Surabaya with 16 students. The research data shows that (1) Alare application is declared valid as indicated by the mode of content validity and construct validity of 4 with the valid category, (2) Alare application is declared practical as indicated by the average results of student response questionnaires, which are supported by student activity observations, amounting to 89.2% with very practical criteria, (3) Alare application is declared effective based on the increase in the acquisition of pretest and posttest scores of critical thinking skills and also the completeness of students' learning outcomes. The value of students' critical thinking skills based on the N-gain score increased because the medium-g and high-g criteria were obtained. The completeness of students' learning outcomes in both individual and classical completeness is significantly complete with a percentage of 100%. Based on this, it can be concluded that the Alare application is feasible to use to train students' critical thinking skills on reaction rate material.